2017
DOI: 10.1111/den.12959
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency ablation in patients with large cervical heterotopic gastric mucosa and globus sensation: Closing the treatment gap

Abstract: This is the first study on RFA focusing on therapy of large symptomatic heterotopic gastric mucosa. Hereby, we demonstrate that this new technique can be successfully implemented in patients where treatment was limited so far (NCT03023280).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 28 publications
0
13
0
1
Order By: Relevance
“…The efficacy of PPIs for LPR should be better for acid than non‐acid and mixed reflux, as PPIs do not limit refluxate mechanically but seek only to change its acid content . It has even been suggested that a PPI prescription (as single medication) in non‐acid and mixed LPR could exacerbate laryngopharyngeal mucosa injury from non‐conjugated bile salts, trypsin, etc by providing the required alkaline pH for optimal activity of non‐conjugated bile salts . Thus, it is likely that many LPR patients with non‐acid or mixed LPR did not receive adequate treatment during their initial therapeutic trial.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of PPIs for LPR should be better for acid than non‐acid and mixed reflux, as PPIs do not limit refluxate mechanically but seek only to change its acid content . It has even been suggested that a PPI prescription (as single medication) in non‐acid and mixed LPR could exacerbate laryngopharyngeal mucosa injury from non‐conjugated bile salts, trypsin, etc by providing the required alkaline pH for optimal activity of non‐conjugated bile salts . Thus, it is likely that many LPR patients with non‐acid or mixed LPR did not receive adequate treatment during their initial therapeutic trial.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Kristo et al[78] recently reported an 80% rate of complete macroscopic and histologic eradication after 2 sessions of radiofrequency ablation with im-provements in globus sensation and quality of life without any major adverse events or stricture formation after an approximate 2-year follow-up. The involvement of the esophageal heterotopic mucosa in esophageal pathology may eventually become as popular as BE, which will promote novel technologies such as hybrid-APC that could improve the therapeutic intervention for selected cases of large IPs in the future[83,84].…”
Section: Management and Surveillance Considerationsmentioning
confidence: 98%
“…Other issues such as elevated surfaces[78] or the size of the IP should be taken into consideration before deciding which strategy is most appropriate. For instance, experts generally did not include patients with large IPs in the previously conducted interventional APC trials to exclude the possibility of stricture formation[18,79-81].…”
Section: Management and Surveillance Considerationsmentioning
confidence: 99%
“…Indeed, up to 23% of patients with gastric inlet patch complain of globus symptom 2 and a controlled study reported a significant and sustained symptomatic improvement after argon plasma coagulation of the heterotopic mucosa 17 . Efficacy of radiofrequency ablation in improving globus symptoms has been reported in a small uncontrolled series 18 . Adenocarcinoma, Barrett's esophagus, and Helicobacter pylori are reported as rare consequences of inlet patches 48‐50 .…”
Section: Diagnosis Of Globusmentioning
confidence: 99%